Manajemen Sarana dan Prasarana Pendidikan dI MTSN 2 Karawang - Hermalia, Tita; Baroroh, Niswatun (IAIN Syekh Nurjati Cirebon, 2022)
The purpose of this study was to find out and obtain information about the management of educational facilities and infrastructure at MTsN 2 Karawang. The analytical method used is descriptive qualitative. The research took place at MTsN 2 Karawang in November-December 2021. The principal, vice principal in charge of facilities and infrastructure, maintenance support staff, and students at MTsN 2 Karawang became research informants. Interviews, observations, and reporting studies were all used to collect data. After that, the data is analyzed by reducing it, presenting it, and drawing conclusions. Triangulation of sources, techniques, and hypotheses is a technique of validity. The results show that: (1) Preparation for the management of facilities and infrastructure at MTsN 2 Karawang begins with a work meeting and the preparation of an activity agenda led by the principal, then maintenance is divided into 2 categories, namely periodic maintenance and routine maintenance. Then prepare a one-year budget plan made by the school principal and the Budget Drafting Team. Furthermore, representatives from the field of facilities and infrastructure specifically choose the structure of the maintenance of facilities and infrastructure, as well as their respective job desks in each division, which are known by the principal. The final step is to socialize students at school. (2) School maintenance processes and techniques begin with frequent and routine maintenance. Routine maintenance includes the maintenance of classrooms, teacher offices, and special rooms such as libraries, computer laboratories, and science laboratories. The school also performs routine maintenance on air conditioners, printers and copiers, as well as upgrades computer programs. (3) Obstacles faced by schools in preparing for repairs to facilities and infrastructure, including problems that arise unexpectedly and require immediate repair of these facilities. The lack of knowledge of users of school facilities and infrastructure, partnering with external parties who are often less sensitive, and cultural differences between individuals in the use of facilities and infrastructure are among the process and technological obstacles faced. including problems that arise unexpectedly and require immediate repair of these facilities. The lack of knowledge of users of school facilities and infrastructure, partnering with external parties who are often less sensitive, and cultural differences between individuals in the use of facilities and infrastructure are among the process and technological obstacles faced. including problems that arise unexpectedly and require immediate repair of these facilities. The lack of knowledge of users of school facilities and infrastructure, partnering with external parties who are often less sensitive, and cultural differences between individuals in the use of facilities and infrastructure are among the process and technological obstacles faced.